HERMENEUTIC ANALYSIS OF ARTICLES 281 AND 286 OF THE LAW ON BANKRUPTCY AND SUSPENSION OF DEBT PAYMENT OBLIGATIONS FROM THE PERSPECTIVE OF LEGAL CERTAINTY - Biner Sihotang; Mesa Indra Naiborhuo (Sekolah Tinggi Ilmu Hukum Awang Long, 2026)
This study analyses the conflict between the absolute rights of separate creditors under the Law on Mortgage Rights (UUHT) and the collective mechanisms under the Law on Bankruptcy and Suspension of Debt Payment Obligations (UUK-PKPU), particularly in relation to the implementation of Articles 281 and 286. The main problem arises when separate creditors who reject the settlement plan are still forced to accept the results of majority voting, thereby degrading absolute security rights into mere quasi-secured claims. Using normative juridical methods and Gadamer’s fusion of horizons legal hermeneutics, this study examines the interpretative tensions and legislative gaps that deviate from the original intent of the 2004 law. The results of this study show that this inconsistency in norms creates legal uncertainty that has a systemic impact on the banking sector through portfolio risk escalation and increased cost of funds, which ultimately erodes the stability of the national investment climate. This study recommends amending the UUK-PKPU to include the Objection Right and Opt-Out Right mechanisms, and standardising the substantive justice test applied by commercial judges to ensure the protection of the economic value of collateral. This regulatory reconstruction is crucial to restoring the spirit of legal certainty and strengthening Indonesia’s global economic competitiveness.